ANALISIS BERPIKIR KRITIS SISWA BERGAYA KOGNITIF PADA PEMBELAJARAN BIOLOGI MELALUI MODEL PEMBELAJARAN CIRCUIT LEARNING DENGAN MEDIA VISUAL - Sudiana Sudiana; Imas Cintamulya (Program Studi Pendidikan Biologi, 2018)
ABSTRACT At this time in the learning that is applied in sekolahan most aspects of critical thinking skills of students less become the center of attention by the teacher as well as with aspects of cognitive style of students. This study aims to describe the critical thinking skills of cognitive-style students on biology learning through learning model of Circuit Learning with Visual media. The subjects in this study were students of class VIII-B MTS SYI'AR ISLAM Maibit Rengel consisting of 15 students of cognitive impulsive style, 11 students of accurate cognitive style, 4 students of reflective style, 2 cognitive-style students slowly inaccurate. This study is a descriptive study with the subject of the respiratory system. Critical thinking skills data were obtained from the critical thinking test sheet from Ennis's critical thinking skills indicator and cognitive style data obtained from cognitive style tests referring to the Matching Familiar Figures Test (MFFT) cognitive style instrument developed by Warli (2010). From the results of data analysis, students with cognitive style accurately have a higher critical thinking ability compared with other cognitive-style students. Thus it can beconcluded that there are differences about students' critical thinking skills in accordance with the cognitive style possessed by students through the application ofCircuitLearning model on biology learning. Keywords: Critical Thinking, Cognitive Style, Learning Circuit Learning Model, and Visual Media.